World society and the convergence of consumer values: Buying patterns of eco-certification in the UAE - Mook, Anne (2023)
Eco-certifications offer consumers the opportunity to vote with their money for more sustainable methods of production. While consumer-facing eco-labels are mostly recognized and consumed in western countries little is known about their performance in expat societies. This study applies world society theory to a sample of Arab, Western, and South Asian United Arab Emirates (UAE) residents to test whether globalization causes assimilation of familiarity, attitudes, and buying frequencies for major eco-labels. The results show that respondents with Western ethnicities are more familiar with eco-certifications. However, Arab, and South-Asian citizens report similar or higher levels of importance for the purported benefits of eco-certifications. Among respondents familiar with eco-certification, we found no differences in buying frequency by ethnic group. Findings related to ethnicity support world society theory because social, environmental, and quality ideals converge among different ethnic groups in the UAE.